The Development of Local Wisdom-Based CAI Media for Mathematics Learning at Elementary School - Riana, Desy Dwi; Putriani, Ida (Universitas Pendidikan Ganesha, 2021)
The modernization in education demands a renewal of the learning process. There needs to be an effort to create interactive and fun IT-based learning. Then, the fourth grade students are proficient and excited to operate computers, but the teacher has not fully integrated computers into the mathematics learning process. So, it is necessary to have computer-based learning media with a real context of local local wisdom. The objectives of this study are (1) to produce valid and interesting IT-based learning media (2) to create contextual mathematics learning that is integrated with local wisdom. This is development research which carried out using the ADDIE (Analyze-Design-Develop-Implement-Evaluate) model. The subjects of this study were fourth grade students. The techniques used to collect data were observation, interviews, and questionnaires. Data were analyzed quantitatively and qualitatively. CAI media is made with adobeflash which contains material, practice questions, evaluation, and two interesting games. Based on the results of the media expert's assessment, CAI media was considered feasible with a percentage of 83.9%, while from the material expert's assessment, it was obtained 90.6% in the very feasible category. It can be concluded that the developed CAI media can be applied in the learning process. The implication of this research is that the existence of this learning media can help students understand the subject matter and realize IT-based learning.